2014
DOI: 10.2807/ese.19.22.20823-en
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and impact of a new live attenuated influenza vaccine programme in England: early results of a pilot in primary school-age children, 2013/14 influenza season

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 6 publications
7
25
0
Order By: Relevance
“…Indirect effects were strongest among individuals aged 65 years or older – the age group most vulnerable to influenza hospitalization and mortality. The magnitude of indirect effects we observed is similar to those of other SLIV interventions [21,22,3234] and of interventions vaccinating children at any location [62]. In addition, our results are highly consistent with mathematical models, which project that an increase from 40 to 60% coverage in children aged 6 months to 18 years would reduce influenza hospitalization among adults over 19 years by 33-36% [15].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Indirect effects were strongest among individuals aged 65 years or older – the age group most vulnerable to influenza hospitalization and mortality. The magnitude of indirect effects we observed is similar to those of other SLIV interventions [21,22,3234] and of interventions vaccinating children at any location [62]. In addition, our results are highly consistent with mathematical models, which project that an increase from 40 to 60% coverage in children aged 6 months to 18 years would reduce influenza hospitalization among adults over 19 years by 33-36% [15].…”
Section: Discussionsupporting
confidence: 85%
“…Prior studies reported that SLIV programs increased influenza vaccination [1726] and decreased school absence [1720,2729] and student illnesses [17,20], and some studies report that their economic benefits likely outweigh the cost of program delivery [30,31]. There is some evidence that SLIV programs can produce community-wide indirect effects among pre-school aged children and adults; however, other studies have produced conflicting results [21,22,3234]. Many prior SLIV evaluations did not use randomization or multivariate matching to select a comparison group and are subject to confounding [18,19,21,22,2729,3234]; those that have used more rigorous designs did not measure health outcomes [2426,35,36] or enrolled small numbers of schools [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, vaccination can also reduce transmission and provide indirect protection to vulnerable populations [24]. Vaccination of school children provides direct protection for the recipients and indirect (herd) protection for the community [25][26][27][28], and vaccinating HCWs reduces influenza transmission to vulnerable patients [29][30][31]. Indeed, quantification of the direct and indirect effects of influenza vaccination suggest that for complications such as death due to influenza, which occur much more frequently in unvaccinated elderly populations, indirect benefits can surpass direct ones by a factor of at least 20 [32].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, we do not consider economical due to the CBR to be more than 1.0. According to the criteria of the public investment analysis proposed by the US government's Office of Management and Budget (OMB), it is recognized that the minimum cost benefit ratio is 1.26 or more considering the excess burden due to tax distortion 11 . However, in other studies, the 1.0 standard is applied, so we will judge it based on the equity level.…”
Section: Discussionmentioning
confidence: 99%